MOLECULAR PROFILING AND ANTIMICROBIAL RESISTANCE PATTERNS OF EXTENDED-SPECTRUM BETA-LACTAMASE-PRODUCING ESCHERICHIA COLI ISOLATES FROM CLINICAL SAMPLES IN SOUTHWESTERN NIGERIA - Akindele, Abiodun A.; Aro, Elizabeth O.; Ojedele, Richard O.; Odewale, Gbolabo; Bolaji, Oloyede S. (FUDMA JOURNAL OF SCIENCES, 2025)
Introduction: Escherichia coli (E. coli) is a Gram-negative that can become true pathogenic. Extended-spectrum Beta-lactamases (ESBLs) are enzymes that make bacteria resistant to antibiotics, posing risks for infections and requiring strict infection control measures.Methodology: A hospital-based study in Southwestern Nigeria (August–November 2020) analyzed 105 Escherichia coli isolates using biochemical tests, EMB agar, and PCR for molecular identification. Antibiotic susceptibility was assessed via the Kirby-Bauer method, interpreted using CLSI criteria. Molecular analysis identified blaCTX, blaSHV, and blaTEM genes. Data underwent descriptive analysis and Chi-square testing, with a p-value
Keywords: Molecular characterization; Extended-Spectrum Beta-Lactamases; Escherichia coli clinical isolates; Southwestern Nigeria